The 1st International Conference on Energy, Power and Environment 2021
DOI: 10.3390/engproc2021012045
|View full text |Cite
|
Sign up to set email alerts
|

Designing of a Hybrid Photovoltaic Structure for an Energy-Efficient Street Lightning System Using PVsyst Software

Abstract: With the depletion of traditional fossil fuels, their disastrous impact on the environment and rising costs, renewable energy sources such as photovoltaic (PV) energy are rapidly emerging as sustainable and clean sources of power generation. The performance of photovoltaic systems is based on different factors such as the type of photovoltaic modules, irradiation potential and geographic location. In this research, PVsyst simulation software is used to design and simulate a hybrid photovoltaic system used to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Many studies have shown that these fossil fuels will be exhausted in the near future [4]. Therefore, many countries (both developed and developing) are planning to transition to renewable energy technologies in order to meet the electricity demand of the growing population and improve utility grid operation [5][6][7][8][9]. Among all renewable energy technologies, the solar PV technology is the most widely used for a number of reasons [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that these fossil fuels will be exhausted in the near future [4]. Therefore, many countries (both developed and developing) are planning to transition to renewable energy technologies in order to meet the electricity demand of the growing population and improve utility grid operation [5][6][7][8][9]. Among all renewable energy technologies, the solar PV technology is the most widely used for a number of reasons [10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] Several developed and developing countries plan to shift to photovoltaic energy to encounter the energy needs of their increasing populations [ 35,36 ] and enhance the efficiency of their national utility networks. [ 37,38 ]…”
Section: Introductionmentioning
confidence: 99%
“…It estimates power generation while accounting for losses caused by the environment, efficiencies of system components, wiring, shading, module mismatches, soiling, reflection, aging, and clipping losses. PVSyst is a newly developed simulation software (launched by Folsom Labs) that combines AutoCad design capabilities with all functionalities of the PV system to help system designers generate a complete design in one software package (Tamoor et al, 2021d;Faiz et al, 2021;Habib et al, 2023b). To perform energy estimations and create 3D models, PVSyst enables the utilization of a single software package.…”
Section: Introductionmentioning
confidence: 99%